Predictor of Visual Impairment Following Paraclinoid Aneurysm Surgery: Special Consideration of Surgical Microanatomy Related to Paraclinoid Structures. Issue 1 (12th October 2020) - Ota, Nakao; Petrakakis, Ioannis; Noda, Kosumo; Miyazaki, Takanori; Kondo, Tomomasa; Kinoshita, Yu; Kamiyama, Hiroyasu; Tokuda, Sadahisa; Tanikawa, Rokuya
Abstract: BACKGROUND: Microsurgical clipping with extradural anterior clinoidectomy (EDAC) for paraclinoid aneurysm is an established technique with good angiographic outcomes, although postoperative worsening of visual acuity remains a concern. Multiple reports show visual acuity deteriorating after clipping, yet the cause remains unclear. OBJECTIVE: To analyze results of asymptomatic paraclinoid aneurysm surgeries treated with EDACs, specifically focusing on the microanatomy of paraclinoid structure dissection. This determined the causes of delayed visual impairment and microsurgical indications. METHODS: Results of the treatment with EDAC of 94 patients with cerebral aneurysm and normal preoperative visual acuity but also full visual fields were retrospectively analyzed. RESULTS: The mean aneurysm size was 6.2 (±3.3) mm. Clipping was performed in 87 cases and trapping in 7 cases. Complete angiographic occlusion was observed in 91 patients. In 26 cases, a postoperative visual deficit occurred. A total of 20 cases exhibited partial visual field deficits, including 5 who were asymptomatic. Visual deficits were only detectable by postoperative ophthalmologic testing. Six showed light perception impairment or blinding. Of the 15 patients with symptomatic partial visual field deficits, 5 showed improvement at follow-up. Visual deficits persisted in 22 patients at the last follow-up. Multivariate logistic regression analysis revealed that medial projecting aneurysm (adjusted odds ratio [OR]: 10.43) and the opening of the carotidoculomotor membrane (adjusted OR: 5.19) were significantly related to visual impairment. CONCLUSION: Excess dissection of carotidoculomotor membranes causes postoperative delayed visual worsening. For treating small, asymptomatic paraclinoid aneurysms, carotidoculomotor membranes should not be opened, and microsurgical clipping should not be performed for preoperative asymptomatic medial projecting aneurysms.